Altered visual functions, macular ganglion cell and papillary retinal nerve fiber layer thickness in early-treated adult PKU patients - Serfozo, Csilla (Mol Genet Metab Rep, 2020)
PURPOSE: Retinal changes are poorly described in early treated phenylketonuria (ETPKU). We aimed to investigate possible visual functional and ocular microstructural changes in adult patients with ETPKU. Optical coherence tomography (OCT) and its angiography (OCTA) data from patients with PKU were compared to healthy controls. METHODS: In this prospective, monocentric, cross-sectional, case-control study 50 patients with ETPKU and 50 healthy subjects were evaluated with OCT and OCTA. Measurements were performed on right eyes. The following visual function parameters were studied: best corrected visual acuity (BCVA), spherical equivalent (SE), contrast sensitivity and near stereoacuity; microstructural parameters: retinal nerve fiber layer thickness (RNFLT), ganglion cell layer (GCC) thickness, focal loss of volume (FLV), global loss of volume (GLV), peripapillary, papillary vessel density (VD), ocular axial length (AL) and intraocular pressure (IOP). RESULTS: Among functional tests there were significant differences in contrast sensitivity at 1.5 (p < 0.001), 6 (p < 0.013), 12 (p < 0.001), 18 (p < 0.003) cycles per degree, in near stereoacuity (Titmus Wirt circles, p < 0.001) and in best corrected visual acuity (BCVA, p < 0.001). A statistically significant, moderate positive linear correlation was observed between BCVA and average Phe levels over the last ten years (β = 0.49, p < 0.001). The average (p < 0.001), superior (p < 0.001) inferior GCC (p < 0.001), the FLV (p < 0.003), GLV (p < 0.001) and the average RNFLT (p < 0.004) values of the PKU group were significantly lower than the controls. The serum phenylalanine level (Phe) in the PKU group negatively correlated with inferior (−0.32, p < 0.007), superior (r = −0.26, p < 0.028) and average (−0.29 p < 0.014) RNFL and with AL (−0.32, p < 0.026). In AL we detected a significant difference (p < 0.04) between the good and suboptimal dietary controlled group. There was no significant difference between the ETPKU and control group in the measured vessel density parameters and in IOP. CONCLUSIONS: Our results suggest that functional and ocular microstructural defects are present in patients with PKU, and some of them may depend on dietary control. The mechanism is unclear, but the correlation indicates the importance of strict dietary control in terms of preservation of retinal functions.